Lesbians on Television New Queer Visibility & the Lesbian Normal - Smith, Kate McNicholas (Intellect, 2020)
The twenty-first century has seen LGBTQ+ rights emerge at the forefront of public discourse and national politics in ways that would once have been hard to imagine. Focusing on the small screens of Europe and North America, "Lesbians on Television" maps the contemporary shifts in lesbian visibility within popular media and, from this, extracts a figure of the new 'lesbian normal' that both helps and hinders those it represents. This book offers a unique and layered account of the complex dynamics in the modern moment of social change, drawing together critical social and cultural theory as well empirical research, which includes interviews and multi-platform media analyses. Structured around five central case studies of popular British and American television shows featuring lesbian, bisexual and queer women characters - "The L Word", "Skins", "Glee", "Coronation Street" and "The Fosters".